Herniarin Mitigates High-Fat Diet-Induced Atherosclerosis in Rats via Regulation of Hyperlipidemia, Endothelial Dysfunction, Inflammation and Oxidative Stress - Lai, Jingyue; Li, Zongyu; Zhang, Ying; Guan, Hao; Ma, Jiancang (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Atherosclerosis is a complex and multifactorial disease characterized by the buildup of plaque within the blood vessels, which can result in severe cardiovascular problems. Objectives: The present study attempted to elucidate the beneficial activities of herniarin against High-Fat Diet (HFD)-induced atherosclerosis in a rat model. Materials and Methods: The HFD-induced atherosclerosis rat model was utilized in the present study and treated with the 50 mg/kg of herniarin for 10 weeks. The simvastatin was utilized as standard drug. The body weight of the animals was assessed in weekly manner during the study. The concentrations of lipid markers, HMG-CoA reductase, collagen and calcium in the rats were assessed using kits. The concentrations of oxidative stress-related markers, inflammation-related markers, endothelial dysfunction markers and liver function enzyme activities were investigated using kits. The heart tissues were excised and employed for the histopathological studies. Results: The present results have proved that herniarin treatment at 50 mg/kg concentration successfully decreased body weight and increased heart weight in the rats. The levels of lipid markers, HMG-CoA reductase, collagen and calcium levels were successfully decreased by the herniarin treatment in the rats with HFD-fed atherosclerosis. Furthermore, it also increased the antioxidant concentrations, reduced inflammatory markers, elevated vasodilator and reduced vasoconstrictor levels in the rats with atherosclerosis. These findings are also corroborated by the results of histopathological analysis. Conclusion: In conclusion, our research shows that herniarin treatment may inhibit atherosclerosis development, lower blood lipids, pro-inflammatory cytokines and oxidative stress and ameliorate HFD-induced atherogenic condition in the rats. Therefore, it was clear that herniarin may produce a favorable therapeutic effect against atherosclerosis caused by a HFD.
Keywords: Atherosclerosis; Dyslipidemia; Endothelial Dysfunction; Herniarin; HMG-CoA; reductase